Various presentations of Meckel’s Diverticulum - Kumar, S.; Singh, Y.P.; Vaidya, P. (Journal of Institute of Medicine Nepal, 2007)
Background: Meckel’s diverticulum is very difficult to diagnose. The aim of this study was to study the various presentations of Meckel’s diverticulum in TUTH in one year. Methods: Retrospective study of nine patients admitted from emergency in one year data was done. Result: In acute abdomen we have to think about Meckel’s diverticulum and its complications. The diagnosis of symptomatic Meckel’s diverticulum is difficult to make, especially in adults. The diagnosis must be considered in anyone with unexplained abdominal complaints, nausea and vomiting, or intestinal bleeding. Journal of Institute of Medicine Vol.27(2) 2005